Aufmerksamkeitslenkung mithilfe Innenraumbeleuchtung im Automobil - Barthel, Maximilian (Spektrum der Lichttechnik, 2020)
This work deals with the investigation and development of a new light function with the help of interior lighting in automobiles. The interior lighting installed in current vehicles is enhanced by an animation, thereby drawing the driver's attention. The design in manual and automatic driving and the further development of the light function is presented with the help of several test subject studies in the simulator and in the real vehicle.